Diretrizes para o tratamento e acompanhamento periodontal durante o tratamento ortodôntico - Correia, Marilia Ferreira; Nogueira, Marianne Nicole Marques [UNESP]; Spolidório, Denise Madalena Palomari [UNESP]; Seabra, Eduardo G. (My University, 2013)
The aim of this paper was to search though a revision of the literature the cares before, during and after the orthodontic treatment in patients with a periodontal disease. The literature shows that the orthodontical treatment in healthy patients brings no risk to the periodontium, although the presence of an active periodontal disease counter indicates the dental movement. Thus, it is extremely important to execute a correct diagnosis of any periodontal alteration and treat them before the beginning of the orthodontical treatment. Besides, during the whole orthodontical treatment is also important to have a periodontal control with periodic reevaluations and at the end of the orthodontical treatment, a new oral hygiene orientation may be needed to finally establish the follow-up of the patient according to the risk of periodontal disease.

Objetivo deste trabalho foi, através de uma revisão da literatura, ressaltar os cuidados antes, durante e depois do tratamento ortodôntico em pacientes com doença periodontal. Diante da literatura exposta, foi possível verificar que o tratamento ortodôntico em pacientes saudáveis não traz nenhum risco ao periodonto, mas a presença de doença periodontal ativa contraindica a movimentação dentária. Por isso, é extremamente importante antes de iniciar a terapia ortodôntica, executar um diagnóstico correto das alterações periodontais e tratá-las; e durante toda a terapia ortodôntica, ter um controle periodontal com reavalia- ções periódicas. Além disso, ao final do tratamento ortodôntico, aconselha-se fazer uma nova orientação de higiene oral e estabelecer a manutenção de acordo com a exposição aos fatores de riscos do paciente a doença periodontal.
Guidelines for periodontal care and follow-up during orthodontic treatment
Keywords: Periodontitis; Orthodontics; Patience care planning; Periodontite; Ortodontia; Plano de tratamento